Bacillus velezensis B105-8, a potential and efficient biocontrol agent in control of maize stalk rot caused by Fusarium graminearum - Wang, Shuang; Jin, Pinjiao; Zheng, Yanyan; Kangkang, Wang; Chen, Jiaxin; Liu, Jiansheng; Li, Yonggang (Frontiers in Microbiology, 2024)
Introduction: Maize stalk rot (MSR), caused by Fusarium graminearum, is the most serious soil borne disease in maize production, seriously affecting maize yield and quality worldwide.Microbial biocontrol agents are the best means of controlling MSR and reducing the use of chemical fungicides, such as Bacillus spp.In the study, a soil-isolated strain B105-8 was identified as B. velezensis (accession No. PP325775.1 and No. PP869695.1), demonstrated a broad spectrum against various pathogens causing maize diseases, which effectively controlled MSR, exhibited a high control efficacy of more than 60% and growth-promoting effect in the pot plant. B105-8 could effectively improve soil urease (S-UE), invertase (S-SC), and catalase (S-CAT) activities. S-NP activity showed an initial increase with a peak of 20337 nmol/h/g, followed by a decrease, but activity remained significantly better than control treatment with chemical fungicides. The application of B105-8 repaired the damage caused by F. graminearum on soil activity. The antifungal compound B-1, extracted from B105-8, was purified using a protein purifier, revealing inhibitory effects against F. graminearum. Mass spectrometry analysis indicated the potential presence of C14 Bacillomycin, C15 Iturin, C15 Mycosubtilin, C17, and C15 fengycin in B-1. In pot experiments, a 5 μL/mL concentration of B-1 exhibited 69% control on MSR, enhancing maize root elongation, elevation, and fresh weight. At 10 μL/mL, B-1 showed 89.0% and 82.1% inhibition on spore production and mycelial growth, causing hyphal deformities.Discussion: This study presents the innovative use of B. velezensis, isolated from maize rhizosphere in cold conditions to effectively control MSR caused by F. graminearum. The findings highlight the remarkable regional and adaptive characteristics of this strain, making it an excellent candidate to fight MSR in diverse environments. In conclusion, B. velezensis B105-8 demonstrated potential as a biocontrol agent for MSR.